A Comparative Review of Alternatives To Custody: Lessons from Finland, Sweden and Western Australia - Eley, Susan (2005)
This report was commissioned by the Scottish Parliament Information Centre for the Justice 1 Committee. The international evidence from Finland, Sweden and Australia relating to the use of imprisonment and direct alternatives to custody will form the basis for a critical examination of proposed actions in Scotland to reduce its prison populations